Women's Participation in Politics According to Islamic Communities in Sabungan Village, Sungai Kanan District, South Labuhanbatu Regency - Lubis, Dini Arti; Maraimbang, Maraimbang (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study was to determine the level of women's involvement in politics among Islamic communities living in Sabungan Village, Sungai Kanan Sub-district, South Labuhanbatu Regency. This research uses qualitative methodology, which is a type of field research that collects information from the target or research subject, commonly called informants or respondents. Data collection tools such as interviews and observations were used. The research findings show that the Islamic community in Sabungan Village has both traditional and modern views regarding women's involvement in Islamic politics. The level of women's political participation in this hamlet is still relatively low, but there is increasing awareness and support from various community groups to become more actively involved. Religion, education, and economics are key factors influencing women's participation. This study confirms that to increase women's political participation, a comprehensive strategy is needed, which includes improving political education and providing support from religious and community leaders.